Computational Analysis Of Incompressible Viscous Flow Over Single And Multi-Element Airfoils - El-Sayed, Omer Ali (2003)
The flow-field around a multi-element airfoil with leading-edge slat and trailing-edge flap in landing configuration was performed as well as the prediction of the time dependent flow over a NACA 0012 airfoil. The two dimensional incompressible Navier-Stokes equations with a numerical method based on the pseudo-compressibility approach was developed to simulate viscous turbulent flow around single and multi-element airfoils. The algorithm uses upwind-biased scheme of third order accuracy for the calculation of the inviscid fluxes, while a second order central differencing is used for viscous fluxes, the equations are solved using Lower-Upper Symmetric Gauss Seidel (LUSGS) scheme. The grids around multi-element airfoil are efficiently generated using a multi-block structure technique.The Baldwin-Lomax algebraic turbulence model is used to consider the effect of turbulence. Computed results for the studied cases were compared with experimental data in terms of surface pressure and lift coefficients which show reasonable agreement. Key Words: Multi-Element Airfoil, Pseudo-Compressibility, Confluent Boundary Layer, Flow Separation, Baldwin-Lomax Turbulence Model